Motet “Jesu, Meine Freude” by Johann Sebastian Bach: Comparative Analysis of Editions of Musical Text - Savon, Dmytro (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance and scientific novelty of the selected subject for the research. In the Ukrainian musicology, the motets written by Johann Bach were mainly studied from the compositional means standpoint, considering the system of polyphony, the role of chorale and fugue in dramaturgy as well as the composition of works. Scientists have not previously researched the motets performance specificity. Meanwhile, motets, particularly the one reviewed in the article “Jesu, meine Freude”, are among the most frequently performed works of the choral repertoire. For the first time in the Ukrainian musicology, three edited versions of the motet “Jesu, meine Freude” are analyzed from the standpoint of historically oriented performance. Based on the study of editors’ comments and source literature (mostly German), the question of compliance of the musical text with the task of performing reconstruction of the baroque vocal and choral style was studied. The aim of the article lies in the need to find out specificity of the editors’ interpretation of motet “Jesu, meine Freude” written by Johann Bach and suitability extent of different edited versions for the historical reconstruction of the vocal-choral style of the German Baroque. During the development of particular article, such methods were utilized: historical — the history of edited versions of “Jesu, meine Freude” motet was traced, comparative — the comparative analysis of three edited versions of motet “Jesu, meine Freude” written by Johann Bach (Franz Wulner, Konrad Ameln and Mykhailo Berdennykov) was completed. Main results and conclusions. According to the completed comparative analysis, the first two of the three considered edited versions are textual, while the third one is adopted for performing. Textual versions are characterized by the preservation of the composer’s text in the smallest details, including comments to clearly identify the extent of changes made by the editor in the text. The peculiarities of the version adopted for performing contain the large amount of remarks added by the editor, covering dynamic shades, strokes, tempo notation, etc. It is noted that the choice of version type is determined by performance goals: to perform the works of Johann Bach in an authentic manner, the conductor should focus on facsimile versions, and if they are absent (as in the case of the “Jesu, meine Freude” motet), the one should use textual type of edited versions. The version developed for performing cannot correspond to the authentic performing, as the first does not reflect specific tendencies of the time when it was created. It is specified that the conductor should be familiar with the peculiarities of fixing the means of performance in the musical text of the Baroque era.